Answer:
We conclude that Tim is correct when he says that the expression x² only yields values that are positive.
Step-by-step explanation:
Given the expression
x²
- Plug in and checking x = 1 and x = -1 in the expression
Putting x = 1 in the expression
x²= (1)² = 1
Putting x = -1 in the expression
x²= (-1)² = 1
Thus, the expression yields the same output '1' when we enter x = 1, and x=-1.
- Plug in and checking x = 2 and x = -2 in the expression
Putting x = 2 in the expression
x²= (2)² = 4
Putting x = -1 in the expression
x²= (-2)² = 4
Thus, the expression yields the same output '4' when we enter x = 2, and x=-2.
- Plug in and checking x = 3 and x = -3 in the expression
Putting x = 3 in the expression
x²= (3)² = 9
Putting x = -1 in the expression
x²= (-3)² = 9
Thus, the expression yields the same output '9' when we enter x = 3, and x=-3.
The reason why the expression x² only yields positive values because the expression is in the square form, and the square of any number will always yield a positive value, no matter whether the input number is negative or positive.
Therefore, we conclude that Tim is correct when he says that the expression x² only yields values that are positive.